Síntese e avaliação da atividade biológica de uma coleção de amidas - Castral, Thaís Corrêa (Universidade Federal de São Carlos, 2006)
The present study describes the preparation of amides containing the methylenedioxyphenyl group and also their activity against the leaf-cutting ant, Atta sexdens rubropilosa, its symbiotic fungus Leucoagaricus gongylophorus and the fall armyworm, Spodoptera frugiperda, larvae. From the bioassays it was observed that N-piperidine-3-(3 ,4 - methylenedioxyphenyl)-2-(E)-propenamide (65) was the most promising as insecticide agent among the compounds studied against S. frugiperda with an LD50=1.07 µg/mg larvae. Amide 65 and N,N-diethyl-3-(3 ,4 - methylenedioxyphenyl)-2-(E)-propenamide (66) were the most active against the symbiotic fungus; and N-pirrolidine-3-(3 ,4 -methylenedioxyphenyl)-2-(E)- propenamide (67) and N-benzyl-3-(3 ,4 -methylenedioxyphenyl)-2-(E)- propenamide (72) against the leaf-cutting ant. Additional studies were necessary to establish the structure activity relationship for piperamides. Thus, Combinatorial Chemistry technologies were employed and a solution-phase synthesis of indexed collection of amides was carried out, identified by Gas Chromatography coupled with Mass Spectroscopy (GC/MS), and screened against S. frugiperda. From this library, the most active compound identified was 1-[4- (trifluoromethoxy)benzoyl]piperidine, A8B1, which was then individually synthesized and evaluated. It has shown a LD50 = 8,15 µg/mg larvae, thus less active than amide 65 against S. frugiperda.
Keywords: Síntese orgânica; Spodoptera frugiperda; Química combinatória; Piperamidas; CIENCIAS EXATAS E DA TERRA::QUIMICA